Study on Automotive Back Door Panel Injection Molding Process Simulation and Process Parameter Optimization - Guoqing Wang; Youmin Wang; Deyu Yang (Advances in Materials Science and Engineering)
A plastic back door car panel was considered as the research object. In order to obtain optimal injection molding simulation parameters, Moldflow2018 is used to simulate injection molding process of plastic back door car panel. Orthogonal experiment is conducted to analyze the influence of injection process parameters on the evaluation index. Melt temperature, mold temperature, cooling time, packing pressure, and packing time are selected as process parameters. Warpage and volumetric shrinkage are taken as evaluation indicators. Test groups are designed to obtain data, and range analysis method is employed to analyze warpage and volumetric shrinkage. Warpage range analysis shows that optimal warpage is 9.3 mm for volumetric shrinkage rate of 14.3%. Range analysis of volumetric shrinkage rate indicates that the best warpage is 8.3 mm for the corresponding volumetric shrinkage rate of 15.05%. A comprehensive evaluation index is established using the gray relational analysis. This analysis shows that warpage is 8.3 mm and volumetric shrinkage rate is 14.2%. Taguchi method is employed to obtain signal-to-noise ratio, while range and variance methods are used for the analysis. Optimal warpage is obtained as 8.2 mm, while the volume shrinkage rate is 10.3%. For a single evaluation index warpage, least squares method and artificial fish swarm algorithm are used to find the optimal parameter combination. Moldflow2018 is employed for simulation verification, and minimum warpage is obtained as 6.405 mm.